AI-Driven fetal distress monitoring SDN-IoMT networks - Ullah, Amin; Ul Haq, Qazi Mazhar; Ullah, Zabeeh; Frnda, Jaroslav; Shahid Anwar, Muhammad (PloS one, 2025)
The healthcare industry is transforming with the integration of the Internet of Medical Things (IoMT) with AI-powered networks for improved clinical connectivity and advanced monitoring capabilities. However, IoMT devices struggle with traditional network infrastructure due to complexity and eterogeneous. Software-defined networking (SDN) is a powerful solution for efficiently managing and controlling IoMT. Additionally, the integration of artificial intelligence such as Deep Learning (DL) algorithms brings intelligence and decision-making capabilities to SDN-IoMT systems. This study focuses on solving the serious problem of information imbalance in cardiotocography (CTG) characteristics with clinical data of pregnant women, especially fetal heart rate (FHR) and deceleration. To improve the performance of prenatal monitoring, this study proposes a framework using Generative Adversarial Networks (GAN), an advanced DL technique, with an auto-encoder model. FHR and deceleration are important markers in CTG monitoring, which are important for assessing fetal health and preventing complications or death. The proposed framework solves the data imbalance problem using reconstruction error and Wasserstein distance-based GANs. The performance of the model is assessed through simulations performed using Mininet, according to criteria such as accuracy, recall, precision and F1 score. The proposed framework outperforms both the basic and advanced DL models and achieves an effective accuracy of 94.2% and an F1 score of 21.1% in very small classes. Validation using the CTU-UHB dataset confirms the significance compared to state-of-the-art solutions for handling unbalanced CTG data. These findings highlight the potential of AI and SDN-based IoMT to improve prenatal outcomes.
Keywords: Neural Networks, Computer; Female; ženské pohlaví; internet věcí; srdeční frekvence plodu; Heart Rate, Fetal; Deep Learning; Cardiotocography; lidé; deep learning; umělá inteligence; monitorování plodu; těhotenství; Internet of Things; Algorithms; Fetal Monitoring; kardiotokografie; neuronové sítě; distres plodu; algoritmy; Pregnancy; Artificial Intelligence; Fetal Distress; Humans